1986
DOI: 10.1002/hep.1840060107
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Evidence for the Presence of Ferritin–Iron in the Biliary System of Patients With Iron Overload

Abstract: Ferritin-like particles were observed in bile canaliculi of patients with iron overload. These particles have been further investigated by: a staining method enhancing the size and contrast of ferritin protein, and electron probe microanalysis detecting the presence of the elements iron and phosphorus. Morphological observation of coated vesicles in the cytoplasm adjacent to the bile canaliculi and coated pits in the canalicular membrane suggests a transport mechanism via membrane-bound organelles. Support is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The expression of TIM-2 in bile duct epithelial cells suggests that it may be involved in the transport of ferritin into or out of bile. Ferritin excretion into bile is believed to involve lysosomal exocytosis, but the mechanisms of excretion are not well defined (47,48). From our studies, it is possible that this process involves TIM-2.…”
Section: Figure 8 H-ferritin Is Internalized By Cells Expressing Timmentioning
confidence: 79%
“…The expression of TIM-2 in bile duct epithelial cells suggests that it may be involved in the transport of ferritin into or out of bile. Ferritin excretion into bile is believed to involve lysosomal exocytosis, but the mechanisms of excretion are not well defined (47,48). From our studies, it is possible that this process involves TIM-2.…”
Section: Figure 8 H-ferritin Is Internalized By Cells Expressing Timmentioning
confidence: 79%
“…114 The form in which iron is released into the bile appears to be variable, and both free iron as well as iron bound to ferritin and Tf have been detected. 92,[112][113][114][115][116][117] A variety of investigations have shown that in addition to endogenous hepatic iron, iron derived from plasma Tf, NTBI, or ferritin, as well as ferritin protein, can be taken up by the liver and rapidly transferred to the bile. 92,[115][116][117] The mechanisms of biliary iron excretion remain poorly characterized but there is some evidence from rats to suggest that ironcontaining lysosomes accumulate at the canalicular membrane and that these are the source of the released iron.…”
Section: Iron Exportmentioning
confidence: 99%
“…Fe-loaded ferritin, comprised largely of Ftl1, was enriched in the bile from Fe-loaded wild-type (and Slc30a10 KO/KO ) mice at levels sufficient to account for all nonheme Fe. While our study did not address the mechanism of Fe export into bile, Fe-loaded ferritin is most likely exported into the bile via lysosomal exocytosis as previously shown ( 16 , 17 , 18 , 19 , 20 , 21 ). Biliary excretion of excess Fe is unlikely to involve nuclear receptor coactivator 4 (NCOA4), as NCOA4 delivers ferritin to lysosomes in Fe deficiency, not excess ( 40 ).…”
Section: Discussionmentioning
confidence: 80%
“…Transferrin and lactoferrin translocate from the blood to the bile ( 13 , 14 , 15 ). Ferritin is present in the bile and originates from lysosomal exocytosis by hepatocytes ( 16 , 17 , 18 , 19 , 20 , 21 ). However, only transferrin is abundant in the bile under physiologic conditions ( 22 ).…”
mentioning
confidence: 99%